2017
DOI: 10.3934/mbe.2017043
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of continuous and intermittent androgen suppression for the treatment of advanced prostate cancer

Abstract: Prostate cancer is one of the most prevalent types of cancer among men. It is stimulated by the androgens, or male sexual hormones, which circulate in the blood and diffuse into the tissue where they stimulate the prostate tumor to grow. One of the most important treatments for advanced prostate cancer has become androgen deprivation therapy (ADT). In this paper we present three different models of ADT for prostate cancer: continuous androgen suppression (CAS), intermittent androgen suppression (IAS), and peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Therefore, a sufficient condition so that Table 1 we find that ϕ b ≈ 33490 kJ and ϕ c ≈ 30485 kJ and, after substituting these values in (7), we get T * b ≈ 4.1 days and T * c ≈ 49.7 days. Then the net energy from equation (6) is A(T * b , T * c ) ≈ 119, 288 kJ.…”
Section: Computing Maximum Net Energy Intakementioning
confidence: 77%
See 4 more Smart Citations
“…Therefore, a sufficient condition so that Table 1 we find that ϕ b ≈ 33490 kJ and ϕ c ≈ 30485 kJ and, after substituting these values in (7), we get T * b ≈ 4.1 days and T * c ≈ 49.7 days. Then the net energy from equation (6) is A(T * b , T * c ) ≈ 119, 288 kJ.…”
Section: Computing Maximum Net Energy Intakementioning
confidence: 77%
“…Our mathematical analysis showed that the net energy intake A is maximized when the total time spent hunting for berries (T b ) and crabs (T c ) is given by (T * b , T * c ) from (7). In our analysis, we assumed that there is an upper bound on γ = T c + T b from (10) and, using our parameters from Table 1, this bound becomes γ < 77.04 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations